KEEFEKTIFAN PEMBELAJARAN MATERI EKOSISTEM MENGGUNAKAN HEURISTIK VEE DENGAN SQ3R - Azizah, Fazat; Sukaesih, Sri (Journal of Biology Education, 2014)
Abstract ______________________________________________________________________________ The aim of this study is to describe the effectiveness of teaching materials dealing with ecosystem by using the Vee Heuristik with SQ3R (Survey, Question, Read, Recite, Revise). This study is a form of quasi experimental with nonequivalen control group design. Sample of this study is chosen based on teacherâs recommendation. The collected data in this study are in the form of studentsâ activitiesÂ  taken by using observation. The result of the study is taken by using test. Teacherâs activities are taken through observation. Studentsâ opinions are collected through questionnaire and the teacherâs opinions are collected through interview. The result of the study shows that the experimental class belongs to active class. Whereas the control class belongs to active class and medium active class. The average of N-gain of the experimental class and the control class is concluded into medium criteria. The mean of N-gain of experimental class isÂ  0,51 which is higher than controll class having the average of N-Gain 0,36. The result of t-test shows that the learning result of experimental class is difficult as the control class .Based on the study, it can be concluded that ecosystem learning used the Vee Heuristic with SQ3R effective in State Junior High School 2 Batang.Abstrak __________________________________________________________________________ Penelitian ini bertujuan untuk mendeskripsikan keefektifan penerapan pembelajaran materi ekosistem mengggunakan Heuristik Vee dengan SQ3R (Survey, Question, Read, Recite and Review). Penelitian ini merupakan penelitian quasi experimental dengan nonequivalen control group design. Sampel penelitian ini diambil berdasarkan rekomendasi dari guru. Data yang diambil dalam penelitian ini berupa data aktivitas siswa dalam pembelajaran yang diambil dengan metode observasi, hasil belajar diambil dengan metode tes, kinerja guru dengan observasi, tanggapan siswa dengan angket dan tanggapan guru dengan wawancara. Hasil penelitian menunjukkan aktivitas kelas eksperimen dalam kriteria aktif sedangkan kelas kontrol termasuk dalam kriteria aktif dan cukup aktif. Rata-rata N-gain kelas eksperimen dan kontrol menunjukkan kriteria sedang. Rata-rata N-Gain kelas eksperimen 0,51 lebih tinggi dari kelas kontrol 0,36. Hasil uji t menunjukkan hasil belajar kelas eksperimen berbeda signifikan dengan kelas kontrol. Berdasarkan hasil penelitian dapat disimpulkan bahwa pembelajaran materi ekosistem menggunakan Heuristik Vee dengan SQ3R efektif diterapkan di SMP Negeri 2 Batang.